2008
DOI: 10.1111/j.1442-200x.2008.02682.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rikkunshi‐to on infantile hypertrophic pyloric stenosis, refractory to atropine

Abstract: DiscussionIt is considered that muscular spasm rather than hypertrophic pyloric muscle accounts for the symptoms typical of IHPS and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Rikkunshi‐to (RKT, TJ‐43) is prepared from eight crude herbs: Atractylodes Lancea Rhizome, Ginseng, Pinellia Tuber, Poria Sclerotium, Jujube, Citrus Unshiu Peel, Glycyrrhiza and Ginger (Table 1). RKT is widely prescribed in Japan for patients with a variety of GI symptoms including anorexia, 5 nausea and vomiting 6,7 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rikkunshi‐to (RKT, TJ‐43) is prepared from eight crude herbs: Atractylodes Lancea Rhizome, Ginseng, Pinellia Tuber, Poria Sclerotium, Jujube, Citrus Unshiu Peel, Glycyrrhiza and Ginger (Table 1). RKT is widely prescribed in Japan for patients with a variety of GI symptoms including anorexia, 5 nausea and vomiting 6,7 …”
Section: Resultsmentioning
confidence: 99%
“…One case report illustrated that oral administration of RKT stopped the vomiting of infantile hypertrophic pyloric stenosis refractory to atropine, possibly by improving gastric motility and restoring normal gastric myoelectric activity 7 …”
mentioning
confidence: 99%
“…Rikkunshito, which mimics these ghrelin effects, effectively improved food intake and GI motor activities in this study. Rikkunshito is a traditional herbal medicine used to treat GI tract disorders such as functional dyspepsia 32, 33, 34, 35, 36 and gastroesophageal reflux. 37 Oral administration of rikkunshito increases plasma acyl ghrelin levels in humans, mice, 38 rats 14, 15 and dogs (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Rikkunshito is composed of 8 constituents: Glycyrrhizae radix (4.7%), Zingiberis rhizoma (2.3%), Atractylodis lanceae rhizoma (18.6%), Zizyphi fructus (9.3%), Aurantii nobilis pericarpium (9.3%), Ginseng radix (18.6%), Pinelliae tuber (18.6%), and Hoelen (18.6%). Several studies have shown that many Japanese herbal medicines, including Rikkunshito, improve gastroduodenal motility-related disorders and are therefore clinically efficacious against FD to some extent (10)(11)(12)(13)(14). However, few studies have been reported on the action mechanism of this medicine in humans (15); although Rikkunshito has been demonstrated to improve the impairment in the gastric AR in vitro (16), no clinical reports have been published on the effects of Rikkunshito on the gastric AR.…”
Section: Introductionmentioning
confidence: 99%